BRF1 accelerates prostate tumourigenesis and perturbs immune infiltration - Loveridge C.J.; Slater S.; Campbell K.J.; Noor A. Nam; Knight J.; Ahmad I.; Hedley A.; Lilla S.; Repiscak P.; Patel R.; Salji M.; Fleming J.; et al. (Springer Nature, 2024)
Indexed by WOS/SCOPUS/ERA